Improving Awareness And Early Management Of Hemorrhagic Stroke: Education And Training For Healthcare Personnel In Emergency Units In Hospital - Sitepu, Rahmadani (JURNAL PENGMAS KESTRA (JPK), 2024)
Hemorrhagic stroke is a medical emergency that requires rapid treatment. Education and training are essential to better prepare healthcare personnel in the emergency department (ED) to manage patients. This program was conducted through lectures, interactive discussions, and simulations of hemorrhagic stroke management. The primary goal was to enhance healthcare professionals' understanding of early detection, initial treatment, and management protocols for hemorrhagic stroke in the ED. Evaluation results showed improved healthcare personnel's knowledge after the training, as indicated by increased pre-test and post-test scores. Simulations also demonstrated enhanced skills in handling hemorrhagic stroke patients. Overall, this education and training program successfully improved awareness and competency among healthcare personnel. It is hoped that such training can be conducted regularly to enhance the quality of emergency care.